Galangin prevents aminoglycoside-induced ototoxicity by decreasing mitochondrial production of reactive oxygen species in mouse cochlear cultures. (14th March 2016) - Kim, Ye-Ri; Kim, Min-A; Cho, Hyun-Ju; Oh, Se-Kyung; Lee, In-Kyu; Kim, Un-Kyung; Lee, Kyu-Yup
Highlights: Amikacin results in ototoxicity due to the overproduction of reactive oxygen species. Galangin prevents amikacin-provoked increase in ROS production in cochlear explants. Galangin reduced apoptotic cell death of hair cells in amikacin-treated cochlear explants. Abstract: Amikacin is a semi-synthetic aminoglycoside widely used to treat infections caused by gentamicin-resistant gram-negative organisms and nontuberculous mycobacteria. However, the use of this agent often results in ototoxicity due to the overproduction of reactive oxygen species (ROS). Galangin, a natural flavonoid, has been shown to play a protective role against mitochondrial dysfunction by reducing mitochondrial ROS production. In this study, the effect of galangin on amikacin-induced ototoxicity was examined using cultures of cochlear explants. Immunofluorescent staining showed that treatment of inner hair cells (IHCs) and outer hair cells (OHCs) with galangin significantly decreased damage induced by amikacin. Moreover, pretreatment with galangin resulted in decreased amikacin-provoked increase in ROS production in both types of hair cells by MitoSOX-red staining. Attenuation of apoptotic cell death was assessed immunohistochemically using active caspase-3 antibody and with terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay, compared to explants exposed to amikacin alone ( P  < 0.05). These results indicate that galangin protects hair cells in the organ of Corti from amikacin-induced toxicity by reducing the production of mitochondrial ROS. The results of this study suggest that galangin can potentially be used as an antioxidant and antiapoptotic agent to prevent hearing loss caused by aminoglycoside induced-oxidative stress.